إزالة المركبات الفينولية من ماء الجفت (ماء معاصر الزيتون) باستخدام الفحم الفعال ذو المنشأ الخشبي (Latakia University Journal -Basic Sciences Series, 2014)
يعدّ حمض 4,3- ثنائي هيدروكسي البنزوي كأحد أهم المركبات الفينولية التي تتواجد في مختلف مياه الصرف الصناعي ومنها ماء الجفت والذي يتميز بصعوبة تفككه في البيئة.يهدف هذا البحث إلى دراسة الخصائص الامتزازية لأحد أنواع الفحم الفعال التجاري من خلال تطبيق نموذجي لانغموير ((Langmuir isotherm وفريندليتش(Freundlich isotherm) الرياضيين على امتزازحمض 4,3- ثنائي هيدروكسي البنزويكعلى الفحم الفعال بتغير عاملين هما التركيز الابتدائي للمركب الفينولي في المحلول وتغير الحجم الحبيبي للفحم الفعالA: (1000-2000), B: (500-1000), C: (250-500), D: (125-250)mm. حسب السطح النوعي للفحم المدروس (736.7189 m2/g).تم الحصول على منحنيات امتزاز المركب الفينولي المدروس على الفحم الفعال.بتطبيق علاقة لانغموير الخطية تم إيجاد سعة الطبقة الأحادية للحجوم الحبيبية المدروسة للفحم الفعال (A,B,C,D) والتي أخذت القيم (0.36,0.23,0.34,0.35mmol/g)على التوالي،كما أخذ ثابت فريندليتش Kf(المتعلق بالسعة الامتزازية)للحجوم الحبيبية الأربعة (A,B,C,D)القيم (0.75,0.61,0.76,0.79mmol/g)على التوالي. أظهرت النتائج أن الفحم المدروس يشكل مادة مسامية قادرة على إزالة المركبات الفينولية من الأوساط المائية.3,4-dihydroxybenzoic acid is one of phenolic compounds that exists in olive mill waste water (OMWW) and different industrial wastewater.Commercially activated charcoal was studied as absorbent of polyphenols. The value of specific surface area was 736.7189 m2/g. Equilibriums of 3,4-dihyroxybenzoic acid from aqueous solutions on four different particle sizes of the adsorbent with diameters ranged A(1000-2000), B(500-1000), C(250-500), D(125-250)mm was examined at different initial concentrations ofabsorbate. The experimental data were analyzed using the Langmuir and Freundlich isotherm models. Both the isotherm models fit the adsorption data. Monolayer absorption capacities Q0 calculated from Langmuir equation were (0.36, 0.23, 0.34, 0.35mmol/g) for the different granular activated carbon sizes (A,B,C,D) respectively. The values of constant Kf calculated from Freundlich equation were (0.75, 0.61, 0.76, 0.79mmol/g) for the four sizes of granular activated carbon (A,B,C,D) respectively. The results show that the charcoal activated carbon can be used as absorbent for polyphenol compounds.